2005
DOI: 10.1002/ejoc.200400910
|View full text |Cite
|
Sign up to set email alerts
|

The P‐Stereocontrolled Synthesis of PO/PS‐Chimeric Oligonucleotides by Incorporation of Dinucleoside Phosphorothioates Bearing an O‐4‐Nitrophenyl Phosphorothioate Protecting Group

Abstract: The synthesis of protected model dinucleoside (3',5')‐O‐aryl phosphorothioates, their separation into pure diastereomers, and their successful incorporation into oligonucleotides followed by stereospecific deprotection of the O‐aryl phosphorothioate function with oximate ion (inversion) enables the preparation of chimeric PO/PS‐oligonucleotides with a predetermined sense of P‐chirality at each internucleotide phosphorothioate position. The absolute configuration at the phosphorus of the internucleotide O‐aryl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The mechanism of inversion process at the phosphorus atoms of tricoordinate organophosphorus compounds has not been fully clarified. In particular, little is known about the mechanism of the inversion process of phosphorus-containing chiral heterocyclic compounds, despite the fact that these compounds have been widely used to synthesize optically pure organophosphorus compounds such as phosphine-based ligands and biologically active compounds. ,, ,, It has been reported that nucleophilic species (e.g., amines, water, Cl − ) and acids (e.g., amine hydrochlorides) accelerate the inversion process, and their repetitive nucleophilic attacks to the phosphorus atom are proposed to be involved. , However, it cannot rationalize the fact that the inversion is also accelerated in the case that the nucleophilic species and the leaving group at the phosphorus atom are different from each other. In addition, CMPT consisting of less nucleophilic components also accelerated the epimerization of the oxazaphospholidines as above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of inversion process at the phosphorus atoms of tricoordinate organophosphorus compounds has not been fully clarified. In particular, little is known about the mechanism of the inversion process of phosphorus-containing chiral heterocyclic compounds, despite the fact that these compounds have been widely used to synthesize optically pure organophosphorus compounds such as phosphine-based ligands and biologically active compounds. ,, ,, It has been reported that nucleophilic species (e.g., amines, water, Cl − ) and acids (e.g., amine hydrochlorides) accelerate the inversion process, and their repetitive nucleophilic attacks to the phosphorus atom are proposed to be involved. , However, it cannot rationalize the fact that the inversion is also accelerated in the case that the nucleophilic species and the leaving group at the phosphorus atom are different from each other. In addition, CMPT consisting of less nucleophilic components also accelerated the epimerization of the oxazaphospholidines as above.…”
Section: Resultsmentioning
confidence: 99%
“…However, access to stereoregular PS-ODNs is still severely limited despite the considerable efforts by many research groups. Currently, these ODNs are available via the oxathiaphospholane method, ,− in which nucleoside 3′- O -(2-thio-1,3,2-oxathiaphospholane) derivatives are used as monomers, though the method has some drawbacks, such as the time-consuming chromatographic isolation of the diastereopure monomers from ca. 1:1 mixtures of diastereomers, relatively low efficiency of the internucleotidic bond formation under strongly basic conditions, and requirement of another set of four nucleoside 3′- O -(2-oxo-1,3,2-oxathiaphospholane) monomers for the synthesis of stereoregular phosphate/phosphorothioate chimeric ODNs (PO/PS-chimeric ODNs) due to the incompatibility of the method with the conventional phosphoramidite method…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been progress toward efficient synthesis and purification of stereo-defined PS oligonucleotides ( 29 , 30 ). A variety of protocols that yield stereo-defined PS linkages in oligonucleotides have been described such as the H -phosphonate method ( 31 ), use of chiral PS dinucleotide building blocks ( 32 ), use of chiral phosphoramidites with the oxazaphospholidine approach ( 26 , 29 , 30 , 33–35 ), and use of a tricyclic P(III) chiral auxiliary ( 36 ). More recently P(V) chemistry has been elegantly used to synthesize chiral phosphorothioates using limonene precursors ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found, however, that instead of the expected ester 10 ( 31 P NMR δ 29.09, 29.12 ppm, diastereomeric ratio ca. 1:1, observed about 5%), the corresponding dithymidyl (3′,3′)-pyrophosphonate (12) [ 31 P NMR δ 24.85, 24.98, 25.1 ppm, 1:2:1 ratio, 85%)] was observed as the foremost product. Pyrophosphonate 12 was, most probably, produced in reaction of the active ester 10 with methylphosphonic acid 11.…”
Section: T H Imentioning
confidence: 99%
“…9 Some of these coupling reagents and their analogues have also been used previously in the phosphorylation of several alcohols and amines. 10 Recently, we also demonstrated that both P III and P V compounds can be efficiently activated with 1,2,4 triazoles 11 or N-hydroxybenzotriazoles 12 in the esterification of methylphosphonates or phosphorothioates.…”
mentioning
confidence: 99%